New Powers and the Distribution of Preferences in Global Trade Governance: From Deadlock and Drift to Fragmentation - Matthew D. Stephen; Michal Parízek (New Political Economy, 2019)
Existing theories make divergent predictions about the impact of new powers on the global political economy. Some argue that a more even distribution of power will erode international cooperation, while others argue that cooperation can continue with the help of international institutions to overcome collective action problems. We argue that this debate overlooks a critical determinant of the shape of power transitions: the distribution of preferences amongst the major powers. It is primarily in the context of divergent preferences that power transitions are likely to give rise to conflict. Moreover, even where preferences diverge, the gains of cooperation provide a strong incentive to continue to pursue goals through multilateralism. This situation leads to forms of institutional change unanticipated by established theories. These include 'deadlock' in expansive multilateral fora, institutional 'drift' as old rules cannot keep up with the changing political and economic context, and 'fragmentation' as countries seek minilateral solutions that reduce preference diversity. We develop this preference-based, institutional argument by examining the distribution of preferences and institutional change at the World Trade Organization (WTO) and its Doha Round, where the power transition is relatively advanced.
Keywords: 330; BRICS; Doha round; fragmentation; global governance; power shift; preferences; rising powers; World Trade Organization